The impact of dental photography in social media platforms on patients’ selection of dentists and type of treatment - Yaser Nizar Alqabbani; Nawaf Khalid Alfhaed; Khaled Fawaz Almasaad; Rahaf Yahya Mahanshi; Faraz Farooqi; Khalifa S. Al-Khalifa; Balgis Osman Gaffar (BMC Oral Health)
Abstract Background Dental photography has many advantages such as improving professional communication, enhancing patient education, and facilitating treatment acceptance. This study investigated the impact of dental photography through social media on patients’ choice of dental care providers. Methods This cross-sectional survey-based study recruited a convenience sample of adult patients attending selected public and private dental facilities in Saudi Arabia. Data was collected using an online self-administered questionnaire. Participants received the link to the questionnaire through social media of their treating dentists. Results A total of 552 completed the survey of whom 289 (52.4%) aged 18–25 years, 291 (52.7%) were males, 336 (60.9%) were bachelors, and the majority 448 (81.2%) had a postgraduate degree. Snapchat was the most commonly used social networking application, n = 190 (34.4%). Females reported they were more likely to report that seeing the previous cases affect their choice of a dentist (2.025(1.253–3.274)) and that social media can affect their choice as well (1.787(1.219–2.621)). While those who never visited the dentist were less likely (0.622(0.395–0.978)) to support the use of dental photography and less likely (0.579(0.362–0.926)) to report that social media affect their choice of a dentist. Instagram was found to be a significant platform for selecting a dentist (OR = 1.132, range; 0.608–2.11) (p-0.05). Conclusion The presence of the dentist in social networking sites and sharing of their pre-post treatment cases can be an effective marketing tool especially among females and Instagram users.